A Histochemical Study of Lungs in Iraqi Weasel Herpestes javanicus - Hussain Mutlak, Baydaa; Abdulmunem Al-Jawadi, Ahmed; Mohammed Mnati, Intidhar (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The current study aimed to identify the histological structure of the lung in Iraqi weasels, Herpestes javanicus. The present study was conducted on 5 samples of weasel animals weighing between 288 and 564 g. The results of the study displayed that the trachea in Herpestes javanicus branches into two branches of the primary bronchi, which are similar in tissue structure to the trachea, and the results also showed that the primary bronchus branch out to be the secondary and tertiary intrapulmonary bronchus, as the cartilaginous rings turn into finger-shaped plates of hyaline cartilage and these cartilaginous plates disappear in the bronchioles, which in turn branch into the terminal bronchioles, which give a branch to the respiratory bronchioles, which in turn branch into several alveolar sacs, which lead to alveoli. The lungs are covered with the parenchymal pleura membrane, which is made up of a thin layer of connective tissue covered with a layer of mesothelial tissue. The study concluded that the lung in weasels exhibits a tissue structure similar to that of other mammals, with some special variations in this species.